Knowledge Mapping for the University: Analysis of Approaches and an Example of Its Use - T. A. Gavrilova; A. V. Kuznetsova; E. Y. Greenberg (Открытое образование (Москва), 2024)
The purpose of the article is to analyze the current research, development and application of knowledge maps for visualizing heterogeneous, disparate, and often hidden knowledge in universities, and discuss the features of the development of maps in higher education institutions.Materials and methods. The market for intellectual services is actively developing in Russia and worldwide, and the methods of express assessment of human capital are extremely relevant. The intellectual capital of universities is one of the most important assets in the dynamic market of educational and consulting services. Research institutes and universities are modern centers of knowledge and technology, where lecturers and researchers accumulate, transfer and produce knowledge, multiplying and replenishing explicit and implicit intellectual assets. Knowledge management helps educational and research organizations to solve the problems of managing intellectual capital, gain a competitive advantage, improve management efficiency, and reduce risks caused by the concentration of knowledge among a small number of experts. The article is devoted to the problem of analyzing new opportunities for promoting and monetizing the intellectual capital of universities through visualization and knowledge mapping. Knowledge maps of university lecturers are a relevant tool to improve the quality of research and marketing communications, as well as positioning in the market of consulting and intellectual services. Knowledge maps of educational institutions and research teams are of particular research interest, since there is no characteristic business desire to protect knowledge from transfer and reproduction in this field.The result of the study is a typology of knowledge maps, which helps to identify patterns, structures and elements necessary for the development of knowledge bases in universities. The authors based on the results of a pilot study give examples of specific maps. Based on an analysis of existing approaches to the typology of knowledge maps and Bloom’s taxonomy, a hierarchical model reflecting different levels of understanding when interpreting and using knowledge maps was developed. The main research methodology relies on fairly well developed and widely used in the world practice knowledge engineering methods – knowledge extraction, structuring and formalisation. A separate analysis of potential consumers (or stakeholders) of knowledge maps was carried out based on stakeholder theory.Conclusions. The article discusses the methodological aspects of the development and features of the practical application of knowledge maps in higher educational institutions. Knowledge analysis makes it possible to develop the organizational “memory” of a university, collecting strategic knowledge and identifying critical knowledge, and generally enriches the knowledge structure. Knowledge maps as a category of special visual tools used to analyze the knowledge and competencies of university lecturers can improve the process of managing employee competencies, management decision making, and thereby reducing cognitive load. Such maps increase the image and marketing performance of a university in the educational services market, and make the professional landscape of knowledge more transparent.